An Excavation of a Shell-midden at Pallemalla in Southern Littoral area of Sri Lanka: Some Evidence of Prehistoric Chenier Occupation in c. 4th millennium BC - Raj Somadeva; Sudevi Ranasinghe (Ancient Asia, 2006)
A rescue excavation conducted in a prehistoric shell-midden identified in the littoral area of southern Sri Lanka had revealed a substantial set of information pertaining to the coastal adaptation of the prehistoric communities in Sri Lanka in c. fourth millennium BC. Seven human skeletons were excavated. The faunal remains associated with the prehistoric levels at the site show a wide range of exploitative selection of the prehistoric subsistence pattern in the dry-arid maritime littoral eco zone of the country. The article presents a preliminary account of the discovery.